Analysis of the Impact of Government Fiscal and Monetary Policies on Economic Growth in Indonesia: Government Economic Approach - Hanipah Hanipah; Pegi Sugiartini; Indi Millatul Maula (International Journal Labs, 2023)
Government economics is the study of how government policies influence a country's economic activities. In this case, fiscal and monetary policies are the two main instruments used by the government to control economic growth. In Indonesia, fiscal and monetary policies are used to increase economic growth and overcome economic problems faced by the country. Qualitative methods that can be used in this research are case studies or field research. This research aims to analyze the influence of fiscal and monetary policy on economic growth in Indonesia. The research results show that fiscal and monetary policies have a significant effect on economic growth in Indonesia. Fiscal policy, as measured by the ratio of government debt to GDP and government spending, has a positive influence on economic growth. that fiscal and monetary policies have a significant influence on economic growth in Indonesia. Fiscal policy, particularly government spending on infrastructure projects and social programs, has a positive impact on economic growth. Meanwhile, monetary policy, such as interest rate policy and banking regulations, has a less significant influence.